M-government services for rural SMEs. (7th August 2009) - Ntaliani, Maria; Costopoulou, Constantina; Manouselis, Nikos; Karetsos, Sotiris
The scope of this paper is twofold: firstly, to propose a framework that serves the public agencies in identifying potential m-government services to rural SMEs as well as a set of technical solutions for the provision of them; secondly, to present a web-based observatory that can help rural SMEs in finding accurate and updated information for the provided m-government services and being trained at anytime in using them. Also, security issues have been considered regarding the provided services, so that government agencies and users can trust them and feel confident in using them.